University educational architecture design process - Paths and stages of work by specialists at Ufal, Alagoas (International Seven Journal of Multidisciplinary, 2023)
This article presents and analyzes the processes of university educational building projects - their concepts, paths, and parameters produced at the Federal University of Alagoas - Ufal (post-Reuni, from 2013 to 2023). This period was defined by the existence of more accurate data on the conduct of these projects. This research sought to bring discussions about the professional practice of architects and urban planners dedicated to public educational works projects that involve large investments, working time, and specific technical knowledge. We sought to contextualize the situation of Ufal's infrastructure, focusing on the work of the architect and urban planner. The theoretical framework addresses the systematic advancement of organized steps that contribute to professional project work. From this, a descriptive analysis was carried out on the designer's role in the public sphere and their activities and responsibilities. To compare the theoretical framework, interviews were carried out with Ufal professionals, to obtain information about the most important aspects of the team's design work. The challenges, procedures, software used, institutional needs, and demands were discussed in the day-to-day lives of these professionals. At the end of the analysis, forms of collective work, design stages, and restrictions of architectural projects were detailed. The article ends with the need to develop more studies, which can explain the difficulties and characteristics of the urban architect's role in public educational architecture in Brazil. Great limitations were perceived regarding legal requirements and investments made available for creation, aesthetic innovation, adequate technical execution, specification of materials, and durable equipment.